Комплексний підхід до управління внутрішніми процесами в системі публічного управління: комунікативний, операційний та офісний менеджмент - Плотніченко, Світлана Романівна; Plotnichenko, Svitlana; Вороніна, Юлія Євгенівна; Voronina, Yuliia; Ортіна, Ганна Володимирівна; Ortina, Hanna (My University, 2026)
UA: У статті здійснено комплексний аналіз управління внутрішніми процесами в системі публічного управління на основі інтеграції комунікативного, операційного та офісного менеджменту. Актуальність дослідження зумовлена необхідністю підвищення управлінської ефективності органів публічної влади в умовах інституційних трансформацій, реформ децентралізації, цифровізації публічного сектору та зростання суспільних очікувань щодо якості, доступності й прозорості публічних послуг. Обґрунтовано, що результативність публічного управління значною мірою залежить від узгодженості внутрішніх управлінських процесів, ефективної організації діяльності апарату, налагоджених внутрішніх комунікацій і оптимізації операційних процедур. Методологічну основу дослідження становлять загальнонаукові та спеціальні методи пізнання, зокрема аналіз і синтез, системний, процесний та структурно-функціональний підходи, що дало змогу виявити взаємозв’язок між ключовими складовими внутрішнього менеджменту в органах публічної влади та обґрунтувати доцільність їх інтегрованого застосування. Визначено роль комунікативного менеджменту у забезпеченні координації управлінських дій, формуванні організаційної культури та підвищенні мотивації персоналу. /// EN: The article provides a comprehensive analysis of internal process management in the public administration system based on the integration of communicative, operational, and office management. The relevance of the study is determined by the need to enhance the effectiveness of public authorities in the context of institutional transformations, decentralization reforms, digitalization, and growing public expectations regarding the quality, accessibility, and transparency of public services. It is substantiated that the effectiveness of public administration largely depends on the coherence and coordination of internal management processes, the efficient organization of administrative activities, well-established internal communi cations, and the optimization of operational procedures within public authorities. The research is grounded on the application of general scientific and special research methods, including analysis and synthesis, as well as systemic, process oriented, and structural-functional approaches. These methodological tools made it possible to identify the interrelationships between the key components of internal management and to justify their integrated application in the activities of public administration bodies. The role of communicative management in ensuring coordination of managerial actions, strengthening internal interaction, shaping organizational culture, and enhancing staff motivation is determined. The significance of operational management as an effective tool for optimizing managerial processes, rational use of human and organizational resources, reducing administrative barriers, and improving the quality of public services is analyzed. Particular attention is paid to office management as the organizational foundation of day-to-day activities of public authorities, which ensures effective document flow, time management, administrative support, and informed managerial decision-making.
Comprehensive approach to managing internal processes in the public administration system: communicative, operational and office management
Keywords: публічне управління; внутрішні процеси; комунікативний менеджмент; операційний менеджмент; офісний менеджмент; органи публічної влади; управлінська ефективність; public administration; internal processes; communicative management; operational management; office management; public authorities; managerial effectiveness